Commentary: Grow Tomorrow’s School Leaders? Plant Some Seeds Today! (LEARNing Landscapes, 2008)
School leadership development has received significant investment in the UK in recent years. Programmes to support leaders at all levels have focussed on national standards, leadership behaviours and capacity building. England is now facing an increasing shortage of headteachers. This article provides a perspective on this situation and offers some practical ideas to school leaders for building approaches to succession planning in their own schools.
Keywords: school leadership; capacity building; leadership behavior; headteacher